Preloaded vs manually loaded IOL delivery systems in cataract surgery in the largest ambulatory surgery center of northwestern China: an efficiency analysis - Wu, Yazhen; Yan, Hong; Yan, Weijia (BMC ophthalmology, 2020)
To compare the efficiency of preloaded vs manually loaded IOL (P-IOL vs M-IOL, respectively) delivery systems in cataract surgery in the largest ambulatory surgery center of Northwestern China.
Gesehen am 19.07.2024